2017
DOI: 10.1111/dme.13547
|View full text |Cite
|
Sign up to set email alerts
|

Family behaviours that have an impact on the self‐management activities of adults living with Type 2 diabetes: a systematic review and meta‐synthesis

Abstract: While most family behaviours are unambiguously perceived by adults with Type 2 diabetes to act as facilitators of or barriers to self-management, some behaviours were perceived as being neither clear facilitators nor barriers; these were termed 'equivocal behaviours'. If the concept of 'equivocal behaviours' is confirmed, it may be possible to encourage the adult living with Type 2 diabetes to reframe these behaviours so that they are perceived as enabling their diabetes self-management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 67 publications
(113 reference statements)
7
57
0
6
Order By: Relevance
“…Despite having been taught how to measure/monitor their blood glucose, four out of ten Pakistani women and half of the Emirati participants reported that selfmeasurements were challenging to do themselves. This is consistent with results of previous studies that have shown that social support plays a vital role in the management of T2DM patients, especially for those with low levels of education [144,242,[249][250][251][252]. To the contrary, the Kurdish participants expressed that they had reasonable control of their measurements and were capable of monitoring their blood glucose independently.…”
Section: Blood Glucose Monitoring and Pharmacological Treatmentsupporting
confidence: 90%
“…Despite having been taught how to measure/monitor their blood glucose, four out of ten Pakistani women and half of the Emirati participants reported that selfmeasurements were challenging to do themselves. This is consistent with results of previous studies that have shown that social support plays a vital role in the management of T2DM patients, especially for those with low levels of education [144,242,[249][250][251][252]. To the contrary, the Kurdish participants expressed that they had reasonable control of their measurements and were capable of monitoring their blood glucose independently.…”
Section: Blood Glucose Monitoring and Pharmacological Treatmentsupporting
confidence: 90%
“…Sociocultural context denotes the within-group beliefs and norms (e.g., shared cultural values, practices, experiences) that influence behavior, cognition, learning, and identity (87). Cultural beliefs and patterns of group or family behavior may also be associated through religion, ethnicity, or social interaction (136). Additionally, attitudes and beliefs of different cultures, which are transferred across generations, are also shaped by historical and social forces (61).…”
Section: Sociocultural Contextmentioning
confidence: 99%
“…Vongmany et al's recent meta-synthesis on family behaviors that have an impact on the self-management activities of adults living with T2D showed that a significant number of familial behaviors are experienced as equivocal. They concluded that it may be possible to encourage adults living with T2D to reframe these behaviors so that they are perceived as enabling their diabetes self-management (Vongmany et al 2017).…”
Section: Introductionmentioning
confidence: 99%